RANCANG BANGUN ALAT PENGADUK MEKANIS DI INDUSTRI KECIPUT - S, FS Nugraheni; Achmad, Laila Faizah; Handayani, Dwi (Universitas Diponegoro, 2014)
Abstract Jenang is unique snack from kudus regency and used as kudus icon which was produced from several small industry,middle industry and big industry that has flexible texture,sweet and long lifetime (approximately 6 month). There are so many obstacles which is faced by small industry with traditional mixer that jenang quality is not too good. The characteristics are inflexible texture,flour flavor in jenang taste and also short lifetime (only 1 month). It is because of each cooking process need 6 – 7 hours and temperature 600 – 700C in the jenang produstion process, so the quality is low. In training and consulting about jenang cooking process explain that to produce better quality of jenang it need cooking period only 4 – 5 hours and temperature 1000 – 1100C. The characteristics of jenang that was produced are more flexible,no flour flavor and long lifetime (in 1 month these product still can be consumed) This training and consulting the industry responses are very good.they also hoped that there will be a follow –up especially in mechanical instrumentation grant for producing jenang. Because small industry still use manual instrumentation in jenang production Keyword : jenang, flexibility,loose of flour flavor Abstrak Jenang merupakan makanan camilan yang khas dari Kudus dan sebagai ikon Kudus yang diproduksi dari berbagai industri kecil,menengah dan besar dengan rasa gurih,lentur,manis dan legit serta mempunyai umur simpan selama 6 bulan. Banyak kendala yang dialami industri kecil dengan alat pengaduk tradisional dimana kualitas jenang kurang baik,diantaranya kurang lentur,rasa tepungnya masih ada dan tidak awet (hanya 1 bulan) karena dalam memproduksi setiap masak membutuhkan waktu 6 – 7 jam dan suhu 600 - 700C hal ini yang menyebakan kualitas kurang memenuhi syarat. Adanya pelatihan dan konsultasi tentang kinerja alat pengaduk mekanis pada proses pemasakan jenang dijelaskan bahwa untuk waktu pemasakan hanya 4 – 5 jam dan suhu 1000 – 1100C menghasilkan jenang kualitas baik yaitu lebih lentur,rasa tepung hilang dan selama 1 bulan ini jenang belum mengeras (masih awet) Pelatihan dan konsultasi ini dilaksanakan sangat diterima para pengrajin dan diharapkan ada tindak lanjut khususnya bantuan alat mekanis pembuatan jenang mengingat pengrajin kecil ini dalam memproduksi jenang masih secara manual Kata kunci : jenang, kelenturan, rasa tepung hilang